N-Heterocyclic carbene catalyzed asymmetric [3 + 3] cycloaddtion of β, β-disubstituted, α, β-unsaturated carboxylic esters with 3-aminobenzofurans. Issue 7 (10th February 2021) - He, Chonglong; Zhou, Yipeng; Li, Zhanhuan; Xu, Jianfeng; Chen, Xingkuan
Abstract : An NHC-catalyzed β-carbon functionalization reaction to afford enantioenriched benzofuran fused δ-lactams bearing an all-carbon quaternary stereocenter is documented. Abstract : An N-heterocyclic carbene (NHC) catalyzed formal [3 + 3] cycloaddition reaction of β, β-disubstituted, α, β-unsaturated carboxylic esters with 3-aminobenzofurans is doucumented, furnishing benzofuran fused δ-lactams bearing an all-carbon quaternary stereocenter with moderate to excellent yields and excellent enantioselectivies. Further gram-scale preparation and synthetic transformation of the cycloadducts demonstrate good practicality and applicability of this β-carbon functionalization reaction.